Disease protection and growth promotion of potatoes (Solanum tuberosum L.) by Paenibacillus dendritiformis. (2nd September 2014) - Lapidot, D.; Dror, R.; Vered, E.; Mishli, O.; Levy, D.; Helman, Y.
<x xml:space="preserve">Abstract</x> One of the challenges in developing plant‐beneficial bacterial agents for agricultural application is ensuring that an effective selection and screening procedure is in place. The sporadic success of using bacterial agents in the field is usually due to the inability of added bacteria to compete with the local microorganisms. In the present study, the effectiveness of Paenibacillus dendritiformis, a unique pattern‐forming, Gram‐positive, soil bacterium, to reduce disease indices and increase yield in potato crops was examined. This bacterium was chosen as a potential agent based on genome analysis carried out in previous studies. In vitro laboratory experiments, as well as three greenhouse and one field experiment, were conducted. The results show that, in agreement with the hypothesis, P. dendritiformis significantly reduced the maceration area of tuber slices infected by Pectobacterium carotovorum subsp. carotovorum, significantly reduced disease indices in greenhouse experiments and significantly increased tuber yield of infected plants in the field. This work demonstrates the potential of preliminary screening based on genome analysis to identify effective biocontrol agents.